2022
DOI: 10.13075/mp.5893.01288
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring surface contamination for thirty antineoplastic drugs: a new proposal for surface exposure levels (SELs)

Abstract: Background: Chemotherapy drugs are widely used to treat cancer, but their active compounds represent a danger for workers who could be exposed to them. However, they aren't yet included in directive CE No. 1272/2008 and the European Biosafety Network has only recommended a limit value of 100 pg/cm 2 for surface contamination. Thus, it is crucial to assess surface contaminations in healthcare environments. Currently, the technique of choice is surface wipe test combined with liquid chromatography tandem mass sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…Similar observations of higher floor contamination with 75th percentiles exceeding the 100 pg/cm 2 threshold were also reported by other authors such as Hedmer et al ( 37 ) for CP and IF contamination in Sweden or Labrèche et al ( 38 ) for FU in Canada. Similar conclusions were recently published by Dugheri et al ( 45 ) who observed higher floor contamination (compared to desktops), and suggested the new surface exposure level of 100 pg/cm 2 (with the exception of bathrooms).…”
Section: Resultssupporting
confidence: 89%
“…Similar observations of higher floor contamination with 75th percentiles exceeding the 100 pg/cm 2 threshold were also reported by other authors such as Hedmer et al ( 37 ) for CP and IF contamination in Sweden or Labrèche et al ( 38 ) for FU in Canada. Similar conclusions were recently published by Dugheri et al ( 45 ) who observed higher floor contamination (compared to desktops), and suggested the new surface exposure level of 100 pg/cm 2 (with the exception of bathrooms).…”
Section: Resultssupporting
confidence: 89%
“…In this respect, we would also like to point out another important factor which contributes to glove permeation. Literature data show that 5-fluorouracil, cyclophosphamide, iphosphamide, and gemcitabine, which are used in greater quantities ( 56 , 57 ), have low molecular weight (MW) (130, 261, 261, and 263 Da, respectively), and which, according to Oriyama et al ( 39 ), increases the glove permeation rate. Besides low molecular weight, these and other authors point to a possible influence of other chemico-physical properties, such as high drug lipophilia (high logarithm of octanol-water partition coefficient, Log P) ( 39 ), which is still controversial ( 58 ), topological polar surface area, and hydrogen bond donor capacity( 59 ).…”
Section: Resultsmentioning
confidence: 99%
“…5-FU -5-fluorouracil; BSF -busulfan; CP -cyclophosphamide; CarboPt -carboplatin; CisPt -cisplatin; OxaliPt -oxaliplatin; CTB -cytarabine; DC -dacarbazine; DNR -daunorubicin; DTX -docetaxel; DXR -doxorubicin; EPIepirubicin; ETP -etoposide; GEM -gemcitabine; FTM -fotemustine; IDC -idarubicine; IP -iphosfamide; IRT -irinotecan; MP -melphalan; MT -methotrexate; MITC -mitomycin C; PTX -paclitaxel; PMX -pemetrexed; TMX -tamoxifen; RTX -raltitrexed; TPT -topotecan; VNB -vinblastine; VNC -vincristine; VND -vindesine; VNR -vinorelbine In this respect, we would also like to point out another important factor which contributes to glove permeation. Literature data show that 5-fluorouracil, cyclophosphamide, iphosphamide, and gemcitabine, which are used in greater quantities (56,57), have low molecular weight (MW) (130, 261, 261, and 263 Da, respectively), and which, according to Oriyama et al (39), increases the glove permeation rate. Besides low molecular weight, these and other authors point to a possible influence of other chemico-physical properties, such as high drug lipophilia (high logarithm of octanolwater partition coefficient, Log P) (39), which is still controversial (58), topological polar surface area, and hydrogen bond donor capacity (59).…”
Section: Resultsmentioning
confidence: 99%
“…Both Directive 2022/431/EU and the resulting guidelines, "Guidance for the safe management of hazardous medicinal products at work" [9], published in 2023, encourage the development of monitoring methods and biological surveillance for exposed health professionals. While surface contamination sampling remains an important tool to detect incorrect working procedures and increase the awareness of hospital workers [10][11][12][13][14], biological monitoring is still the only way to truly assess occupational exposure and identify possible pathological correlations. Nowadays, ADs can still often be found in the biological fluids of exposed healthcare personnel [15].…”
Section: Introductionmentioning
confidence: 99%